Chemistry through cocrystals: pressure-induced polymerization of C2H2·C6H6 to an extended crystalline hydrocarbon. Issue 10 (27th February 2018) - Ward, Matthew D.; Huang, Haw-Tyng; Zhu, Li; Biswas, Arani; Popov, Dmitry; Badding, John V.; Strobel, Timothy A.
Abstract : The 1 : 1 acetylene–benzene cocrystal, C2 H2 ·C6 H6, was synthesized under pressure in a diamond anvil cell (DAC) and its evolution under pressure was studied with single-crystal X-ray diffraction and Raman spectroscopy. Abstract : The 1 : 1 acetylene–benzene cocrystal, C2 H2 ·C6 H6, was synthesized under pressure in a diamond anvil cell (DAC) and its evolution under pressure was studied with single-crystal X-ray diffraction and Raman spectroscopy. C2 H2 ·C6 H6 is stable up to 30 GPa, nearly 10× the observed polymerization pressure for molecular acetylene to polyacetylene. Upon mild heating at 30 GPa, the cocrystal was observed to undergo an irreversible transition to a mixture of amorphous hydrocarbon and a crystalline phase with similar diffraction to i-carbon, a nanodiamond polymorph currently lacking a definitive structure. Characterization of this i-carbon-like phase suggests that it remains hydrogenated and may help explain previous observations of nanodiamond polymorphs. Potential reaction pathways in C2 H2 ·C6 H6 are discussed and compared with other theoretical extended hydrocarbons that may be obtained through crystal engineering. The cocrystallization of benzene with other more inert gases may provide a novel pathway to selectively control the rich chemistry of these materials.